Implementation of Scientific Learning Approach in Increasing the Effectiveness of PAI Learning in the 2013 Curriculum at Senior High School - Purba, Abdul Malik Khairuddin; Neliwati, Neliwati; Salim, Salim (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This research focuses on implementing PAI Learning with a Scientific Learning Approach in Increasing the Effectiveness of PAI Learning with the 2013 Curriculum at SMA Negeri 3 Tebing Tinggi City, North Sumatra. The purpose of this research was to find out the planning, implementation, and obstacles to learning PAI with a scientific learning approach in increasing the effectiveness of learning PAI. This research method is qualitative research; the sources of this research are primary and secondary, and data collection techniques are observation, interviews, and documentation studies. The data analysis technique of this research is data reduction, data presentation, and conclusion—guarantees for data validity, namely credibility, transferability, dependability, certainty, and triangulation. The results of this study are PAI Learning Planning using the Scientific Learning Approach in the 2013 Curriculum at SMA Negeri 3 Tebing Tinggi City, North Sumatra. It has been made well and implemented optimally, and in the future, it will be even better with more mature preparation; it has been implemented to the fullest by applying the 5M scientific method in learning, namely: Seeing, Asking, Exploring, Associating, and Communicating, Obstacles to Implementation of PAI Learning using the Scientific Learning Approach in the 2013 Curriculum at SMA Negeri 3 Tebing Tinggi City, North Sumatra So far it can be overcome with solutions and cohesiveness.